EATING HABITS AND BODY COMPOSITION OF SCHOOL-AGE CHILDREN FROM A PUBLIC SCHOOL IN THE CITY OF CHIMOIO, MANICA PROVINCE, MOZAMBIQUE - Ivodia Bernarnardo; Amílcar Tovela; Adriano Chiombacanga Nafital; Milagre Américo Pele; Mário Eugénio Tchamo (Artefactum - revista de estudos interdisciplinares, 2026)
Inadequate eating habits are responsible for the increase in Non-Communicable Chronic Diseases (NCDs) worldwide and, in particular, in Mozambique. The present study aimed to assess the eating habits and body composition of school-aged children in a public school in the city of Chimoio, Mozambique. This is a cross-sectional study, with non-probabilistic (convenience) sampling, conducted with 402 children aged 7 to 10 years of both sexes (191 boys and 211 girls). Eating habits were assessed through a semi-quantitative food frequency questionnaire. Data related to anthropometric and body composition parameters were collected, such as body mass, height, skinfolds (triceps and calf), Body Mass Index (BMI), Body Fat Percentage (%BF), Fat Mass (FM), and Lean Mass (LM). The data were analysed using the Statistical Package for the Social Science (SPSS), version 20. The results revealed eating habits characterized by a high intake of vegetables, meat, fish, and nuts. The consumption of ultra-processed foods such as cookies, cakes, sweets and sugary drinks such as soft drinks was highly significant. In addition, the data showed a moderate consumption of dairy products. Girls had a higher mean score of eating habits (32.28 ± 2.55) when compared to boys (31.70 ± 2.37). The sample was 87.4% boys and 85.3% girls with normal weight, with a mean BMI (15.8 ± 1.5 kg/m²). The average %BF was 11.0 ± 3.0%, and a high number of children showed a body fat percentage below adequate levels, corresponding to 76.4% in boys and 82% in girls. The average fat mass was 2.7 ± 1.0 and lean mass (21.8 ± 3.4). Girls had a higher average score for eating habits (32.28 ± 2.55) compared to boys (31.70 ± 2.37). The t-test indicated a statistically significant difference between the sexes (p = 0.018). These results reveal the need for an intervention to improve the situation of these children.